THE ROLE OF TEACHERS IN INCREASING LEARNING INTEREST IN EARLY CHILDHOOD - Nofianti, Rita; Siregar, Maragustam (Tunas Siliwangi, 2025)
The title of this research is "The Role of Teachers in Enhancing Early Childhood Learning Interest." The purpose of this study is to explain how teachers contribute to increasing students' interest in learning. The research method used is qualitative descriptive. The population in this study is referred to as a social situation, consisting of teachers and the school principal. The sampling technique used is purposive sampling. The data collection methods include interviews, observations, and documentation. Data analysis is conducted using qualitative descriptive analysis. The research findings conclude that the teacher's role in increasing students' learning interest consists of three roles: innovator, facilitator, and motivator. As an innovator, the teacher continuously introduces new innovations in the learning process, specifically by implementing the dramatization method. Dramatization is an innovative learning method that can enhance students' interest in learning. As a facilitator, the teacher provides learning materials for students, helping to improve their learning interest. As a motivator, the teacher encourages students to engage in learning, fostering a strong and high level of learning interest.